Pandemic Influenza Virus Surveillance in Portugal: The Laboratory Network for the Diagnosis of Influenza A(H1N1)2009 Infection - Guiomar, Raquel (2012)
In April 2009 a new influenza A(H1N1) virus of swine origin disseminated throughout the world, resulting in the first pandemic of the XXI century. To face the increasing number of diagnosis being requested, a National Laboratory Network for Influenza Surveillance of the new influenza A(H1N1)pandemic virus was activated in Portugal. This is a descriptive study of the Influenza-like Ilness (ILI) cases reported by this network. Association between the variables was evaluated by chi-squared test. Over 62089 ILI cases were notified, 25594 (41.2%) cases were laboratory confirmed A(H1N1)pdm virus, from week 17/2009 to week 15/2010. In the week 33 (summer) were detected 1039 (4.1%) positive cases for A(H1N1)pdm virus although the winter peak occurred in week 46 with 3131 (12.5%) A(H1N1)pdm positive cases. In the age group of 5-14 years old were detected the majority of positive cases 9983 / 15785 (63.0%) opposite in the elderly group (>65 years old) was detected the lower number of A(H1N1)pdm positive cases, 280/2361 (11.0%). The distribution by gender accounts 40.4% of female and 42.3% of male positive cases. The signs and/or symptoms present were analysed revealing that headache (49.7%), cough and myalgies (46.5%) and odinophagia (46.1%) were statistically associated with A(H1N1)pdm positive cases. The chronic pulmonary disease seemed to be more associated with laboratory confirmed A(H1N1)pdm cases. Ninety five strains were isolated and antigenically characterised, 45 were taken for genetic analysis (HA and NA gene). All the strains were antigenically and genetically like the pandemic vaccine strain. It was detected only one strain with the mutation H275Y in the neuraminidase, resistant to oseltamivir. This Laboratory network was an important tool to monitories and control the evolution of the pandemic.